Using “functional hand” protocol to improve hand function following a spinal cord injury: an explorative study: Functional hand protocol: an explorative study - Ciardi, Gianluca; Lamberti, Gianfranco; Avanzi, Martina (Acta Biomedica Atenei Parmensis, 2023)
Background and aim of the work: A cervical spinal cord injury often affects hand control, causing ineffective grasping and handling functions, with a negative impact on patient’s independence and quality of life. Literature recognises scientific evidence only for surgical or instrumental re-education approaches. The purpose of this study is to present the "functional hand" protocol, a physiotherapy tool that, to date, represents a good clinical practice but has no supporting literature.Research design and methods: a longitudinal-single cohort study was conducted at Spinal Unit- Azienda Usl Piacenza. Patients with spinal cord injury at C5-C7 neurologic level, older than 18 years, with correct comprehension of Italian language were recruited. All patients were evaluated with Action Research Arm Test (ARAT) scale to state hand functionality; positive/negative history of Functional Hand protocol was deducted by physiotherapy discharge letters on first spinal unit hospitalisation.Results: six patients were involved in the study; three of them had a positive history of protocol application. ARAT scores differences showed that patients who underwent functional hand protocol had a lower impairment, a better ability to produce cylindrical and cuboid sockets.Conclusions: Functional hand protocol reached a preliminary evidence as effective tool to improve hand recovery in tetraplegic patients; future studies should confirm these conclusions on larger samples, and verify protocol effectiveness in addition to other treatment strategies (functional electric stimulation/ transcranial direct current stimulation/robotic assisted therapy).